Alcohol Exacerbates Murine Pulmonary Tuberculosis - Mason, Carol M. (American Society for Microbiology, 2004)
Alcohol consumption has been described as a risk factor for infection with Mycobacterium tuberculosis, but its contribution to tuberculosis has been difficult to isolate from other adverse socioeconomic factors. Our objective was to evaluate the impact of alcohol consumption on pulmonary infection with M. tuberculosis in a murine model. BALB/c mice were maintained on the Lieber-DeCarli liquid ethanol diet or a liquid control diet and infected intratracheally with low-dose M. tuberculosis H37Rv. Lung organism burdens, lung and lung-associated lymph node CD4(+)- and CD8(+)- lymphocyte numbers and rates of proliferation, and CD4(+)-lymphocyte cytokine production levels were compared between the groups. The alcohol-consuming mice had significantly higher lung organism burdens than the control mice, and the CD4(+)- and CD8(+)-lymphocyte responses to pulmonary infection with M. tuberculosis were blunted in the alcohol group. Lymphocyte proliferation and production of gamma interferon were decreased in the CD4(+) lymphocytes from the alcohol-consuming mice. Additionally, lung granulomas were significantly smaller in the alcohol-consuming mice. In conclusion, murine alcohol consumption is associated with decreased control of pulmonary infection with M. tuberculosis, which is accompanied by alterations in the region-specific CD4(+)- and CD8(+)-lymphocyte responses and defective lung granuloma formation.